2017
DOI: 10.3390/ijms18050919
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Defeats Diabetes-Induced Testicular Damage in Rats Targeting Antioxidant, Inflammatory and Aromatase Expression

Abstract: Antioxidants have valuable effects on the process of spermatogenesis, particularly with diabetes mellitus (DM). Therefore, the present study investigated the impact and the intracellular mechanisms by which thymoquinone (TQ) works against diabetes-induced testicular deteriorations in rats. Wistar male rats (n = 60) were randomly allocated into four groups; Control, Diabetic (streptozotocin (STZ)-treated rats where diabetes was induced by intraperitoneal injection of STZ, 65 mg/kg), Diabetic + TQ (diabetic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 56 publications
10
69
0
Order By: Relevance
“…This study examines the pathogenic mechanism of ROS/JAK2/NFκB under the condition of hyperglycemia. [34][35][36] Similar to these conclusions, in our study, we also found that the testis weight and sperm motility of DM rats were significantly lower than that of normal rats, and the seminiferous tubules of DM rats were found to be damaged through Wright-Giemsa staining. The above experimental data indicate that DM is indeed prone to impaired reproductive function and spermatogenesis, which is consistent with reports by Maresch CC…”
Section: Discussionsupporting
confidence: 89%
“…This study examines the pathogenic mechanism of ROS/JAK2/NFκB under the condition of hyperglycemia. [34][35][36] Similar to these conclusions, in our study, we also found that the testis weight and sperm motility of DM rats were significantly lower than that of normal rats, and the seminiferous tubules of DM rats were found to be damaged through Wright-Giemsa staining. The above experimental data indicate that DM is indeed prone to impaired reproductive function and spermatogenesis, which is consistent with reports by Maresch CC…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of motile sperms was assessed under 400X magnification in at least 10 microscopic fields and being 200 sperms per rat were evaluated. 21 Sperm viability evaluated using eosin-nigrosin staining method. Briefly, 10µL of sperm suspension gently mixed with 10µL eosin-nigrosin solution (containing an equal volume of 1.67% eosin Y and 10% nigrosin) and a smear of the suspension was performed and dried at room temperature.…”
Section: Sperm Evaluationmentioning
confidence: 99%
“…Several preclinical studies and some clinical reports have demonstrated the favorable euglycemic control, antioxidant, anti-inflammatory, immunomodulatory, anti-dyslipidemic, anti-atherogenic, and broad tissue protective effects of TQ, which collectively appear to be of value in improving DM therapy and alleviating its serious multi-organ complications [15,16,17,18,19,20,21]. In addition, a large body of reports has evidenced that TQ is a highly safe natural agent with no serious toxicity [13,14].…”
Section: Introductionmentioning
confidence: 99%